(untitled) (Eurasian Journal of Engineering and Technology, 2026)
The judicial and prosecutorial systems of Uzbekistan have evolved through distinct historical phases: pre-Soviet traditional justice rooted in Islamic shariah and customary law, the centralized Soviet socialist model (1924–1991), early post-independence continuity with limited reforms (1991–2016), and radical modernization since 2017 under President Shavkat Mirziyoyev. This article traces these developments, highlighting the shift from executive-dominated structures to a more independent judiciary aligned with democratic principles, rule of law, and international standards. It examines key legislative milestones, institutional changes, and ongoing challenges, drawing on constitutional, historical, and legal sources.